Modules: M+M = N+N then M=N

Hi. I'm trying to prove this "little fact": let M, N be finitely generated modules over a PID. Then if M+M=N+N (where = means isomorphism and + means direct sum) then M=N.

I'm sure it can be done with the structure theorem (it is obvious from the hypotheses); it looks like it should be trivially proven, but alas, I don't think it can be.

What do you think?

Cheers,
 
EDIT: this isn't true the way I originally thought it was....thinking harder!

Well it's certainly not true without the finitely generated over a PID hypothesis (just think about free abelian groups of infinite rank), so I'm guessing it's some particular property of finitely generated modules over PIDs. The structure theorem immediately comes to mind.
 
M + m = n + n.
2m = 2n
m = n
 

The Physics Forums Way

We Value Quality
• Topics based on mainstream science
• Proper English grammar and spelling
We Value Civility
• Positive and compassionate attitudes
• Patience while debating
We Value Productivity
• Disciplined to remain on-topic
• Recognition of own weaknesses
• Solo and co-op problem solving
Top